Use of troponin to diagnose periprocedural myocardial infarction: effect on composite endpoints in the British Bifurcation Coronary Study (BBC ONE). Issue 19 (31st July 2012) - Cockburn, James; Behan, Miles; de Belder, Adam; Clayton, Tim; Stables, Rod; Oldroyd, Keith; Curzen, Nick; Hildick-Smith, David
Abstract : Background: Periprocedural myocardial infarction (PMI; ESC/ACC type 4a) is diagnosed on the basis of elevation of cardiac enzymes more than three times the 99th centile upper reference limit. Recent guidelines recommend the use of troponin instead of creatine kinase (CK) to diagnose PMI, but this assay increases diagnostic sensitivity, while the clinical significance of small increases in troponin remains undetermined. We examined the effects of using the new definition on the incidence of a composite endpoint (previously defined by CK) in a contemporary clinical randomised trial—the British Bifurcation Coronary Study (BBC ONE). Methods: The BBC ONE trial randomly allocated 500 patients with coronary bifurcation lesions to either a simple or complex stenting strategy. The composite primary endpoint (CPEP) included death, myocardial infarction (MI) (PMI plus subsequent MI) and target vessel failure, at 9 months. Results: In BBC ONE the CPEP occurred in 8% versus 15.2% in the simple and complex groups, respectively (HR 2.02, 95% CI 1.17 to 3.47, p=0.009). This difference was largely driven by PMI, which occurred in nine (3.6%) versus 28 (11.2%) patients (HR 3.24, 95% CI 1.53 to 6.86, p=0.001). Using troponin, PMI would have occurred in 71 (28.4%) versus 114 (45.6%) patients, respectively (HR 1.61, 95% CI 1.27 to 2.05, p=0.001), and the CPEP in 32% versus 48% of patients (HR 1.50, 95% CI 1.2 to 1.87, p=0.001). Use of troponin increased MI detection fivefold, from 7.4% to 37.0% overall. Conclusions: Use of troponin would have led to a fivefold increase in diagnosis of PMI in the BBC ONE trial. Incorporation of PMI into a composite endpoint may no longer be justified in many interventional trials.